Paradigma Kebijakan Kriminal dalam KUHP Nasional Indonesia - Zul Khaidir Kadir (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Indonesia’s new Penal Code (Law No. 1 of 2023) has been promoted as a milestone of legal modernization and decolonial reform, marking a formal break from colonial criminal law. This article critically examines whether such claims correspond to a substantive transformation in criminal policy or merely reflect a reconfiguration of long-standing penal rationalities. Employing normative legal research with statutory and conceptual approaches, the study analyzes the architecture of criminalization and sentencing embedded in the new Code as an integrated system of penal governance. The analysis reveals that although the Penal Code introduces clearer structures, explicit sentencing purposes, and diversified sanctioning mechanisms, these reforms do not substantially alter the state-centered orientation of criminal law. Patterns of expansive criminalization, broad protection of state interests, and flexible sentencing rationales continue to normalize penal intervention as a primary tool of social regulation. Consequently, modernization within the new Penal Code operates largely at the formal and symbolic level, while the underlying paradigm of criminal policy remains oriented toward the consolidation rather than the limitation of punitive state power.